(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2021)
INTRODUCTION: The objective of this review is to learn about Huntington’s disease, how it affects a person’s performance in all spheres of life and the communicative process. METHODS: This article was prepared through a systematic review of scientific articles published in different databases such as: Science direct, Taylor & francis, Scielo, Pubmed, Revista de neurología, Google scholar, Dialnet and Revista chilena de neuropsicología. RESULTS: 60 articles were preselected, of which 35 were selected for the study. ANALYSIS AND DISCUSSION: The communicative profile in Huntington’s disease is characterized by: a progressive loss of basic motor processes, mainly language and swallowing. CONCLUSIONS: Huntington’s disease is a neurodegenerative disease that presents consequences at the physical, emotional, cognitive, communicative and social levels, which leads to people having a decrease in their quality of life and life expectancy.